Do normal head ultrasounds need repeating in infants less than 30 weeks gestation?. (2nd August 2016) - Kaeppler, Caitlin; Switchenko, Nora; DiGeronimo, Robert; Yoder, Bradley A.
Abstract: Objective : Current head ultrasound (HUS) screening recommendations in preterm infants often include a repeat HUS, regardless of initial findings. The objective of this study is to determine the rate of subsequent severe intraventricular hemorrhage (IVH), ventriculomegaly (VM), or periventricular leukomalacia (PVL) among infants < 30 weeks gestation (EGA) with a normal HUS at day of life (DOL) 4–10. Methods : Retrospectively collected data were analyzed for all infants < 30 weeks EGA cared for in one NICU from 1 January 2010 to 31 August 2014. Infants with severe congenital anomalies were excluded. We reviewed the first three HUSs and last documented HUS. Severe IVH was defined as > Papile grade 2 and significant interval HUS change was defined as development of severe IVH, PVL, or VM. Results : Of the 383 infants who had an initial screening HUS between DOL 4 and 10, 258 (67%) were initially normal and repeat screening was performed in 228 of these. None developed severe IVH on follow-up HUS. One infant developed VM secondary to GBS meningitis, and one developed echogenicity concerning for PVL that later resolved. Conclusions : Among very preterm infants with a normal HUS between DOL 4 and 10, routine follow-up HUS is unlikely to identify a significant change.